2015
DOI: 10.1093/mnras/stv2778
|View full text |Cite
|
Sign up to set email alerts
|

A systematicChandrastudy of Sgr A– I. X-ray flare detection

Abstract: Daily X-ray flaring represents an enigmatic phenomenon of Sgr A ⋆ -the supermassive black hole at the center of our Galaxy. We report initial results from a systematic X-ray study of this phenomenon, based on extensive Chandra observations obtained from 1999 to 2012, totaling about 4.5 Ms. We detect flares, using a combination of the maximum likelihood and Markov Chain Monte Carlo methods, which allow for a direct accounting for the pile-up effect in the modeling of the flare lightcurves and an optimal use of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 52 publications
1
24
0
1
Order By: Relevance
“…In the study discussed above, the authors also show that the cumulative spectrum of the flare emission is observed to be a powerlaw with index ∼ 2.6 (Wang et al 2013). While the production mechanism of flare emission is still poorly understood (e.g., Yuan & Wang 2016), the variability time-scale makes it clear that they originate in localized regions very near the SMBH. This creates many challenges from a theoretical standpoint, as the physics near a SMBH are an extreme in the Universe, leaving their physical origin up for debate.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In the study discussed above, the authors also show that the cumulative spectrum of the flare emission is observed to be a powerlaw with index ∼ 2.6 (Wang et al 2013). While the production mechanism of flare emission is still poorly understood (e.g., Yuan & Wang 2016), the variability time-scale makes it clear that they originate in localized regions very near the SMBH. This creates many challenges from a theoretical standpoint, as the physics near a SMBH are an extreme in the Universe, leaving their physical origin up for debate.…”
mentioning
confidence: 88%
“…The emission from these LL-AGN is very much enigmatic, largely due to the inherent difficulty of separating the various entangled emission components (Wang et al 2013;Li et al 2015). Predominantly, there are two unique radiative X-ray phenomena that characterize the emission from LL-AGN: their extremely low, spatially extended quiescent luminosity, and flares that can briefly increase their luminosity by up to a factor of 100 approximately bidaily (Baganoff et al 2001;Yuan & Wang 2016). Physically, even though these black holes (BHs) are associated with much lower net accretion rates, they may also be associated with strong mechanical feedback phenomena such as giant radio bubbles (McNamara et al 2016) and collimated outflowing winds.…”
Section: Introductionmentioning
confidence: 99%
“…The low level of the X-ray bremsstrahlung emission for a stellar bow shock is not surprising. During the passage of S2 star through the pericentre in 2002, there was no significant increase in the emission of Sgr A* detected (Yuan & Wang 2016). It is worth monitoring the flaring rate during the next passage in early 2018, since some theoretical calculations predict the emission at the level of the quiescent state (Christie et al 2016).…”
Section: X-ray Bremsstrahlungmentioning
confidence: 99%
“…1). For more than a decade it has been known that Sgr A ⋆ also shows flaring activity both in X-rays and IR (Baganoff et al 2001;Goldwurm et al 2003;Genzel et al 2003;Ghez et al 2004;Porquet et al 2003;Bélanger et al 2005;Eckart et al 2004;Marrone et al 2008;Nowak et al 2012;Haubois et al 2012;Neilsen et al 2013;Degenaar et al 2013;Barrière et al 2014;Moussoux et al 2015;Ponti et al 2015a;Yuan & Wang 2016). X-ray flares appear as clear enhancements above the constant quiescent emission, with peak luminosities occasionally exceeding the quiescent luminosity by up to two orders of magnitude (see the blue points in Fig.…”
mentioning
confidence: 95%